Is the Evolution of Energy System Productive Structures Driven by a Physical Principle? - Reini, Mauro; Casisi, Melchiorre (Frontiers in Sustainability, 2021)
The aim of the paper is to identify the consequence of the Constructal Principle in the field of Thermoeconomics of (energy) production systems. This Principle has been recently formulated as an extension of the Maximum Entropy Production Principle and it has been used in literature to explain the shape and structure of all kind of flowing system. First, the concept of Thermoeconomic Environment is defined and discussed in the paper, with the aim of reconciling the Reference Environment, required by the thermodynamic evaluation of all process, and the consumption of environmental resources and residual emissions, which inherently characterize every kind of production system. This approach allows to infer that the evolution of any energy system is strictly related to the exploitation of resources from the Thermoeconomic Environment. When the limitation on the exploited resources does not affect the system the latter evolves toward a continuous increment of the product, consistently with the Malthusian growth. The paper shows that the presence of a recycle allows a further reduction of the unit exergy cost of the product, with respect to the reduction allowed by the components’ efficiency improvement alone. In this way a more sustainable behavior of the macro-system, made up by the production process together with its supply chain, is obtained. The definition of the Thermoeconomic Environment allows (at least in principle) to properly identify the resource (exergy) cost of disposing off residues and sub-products directly in the environment, without any kind of additional operation. Their continuous accumulation in the environment directly implies an increment of the unit resources (exergy) cost of the product, exactly because the exergy stock of the Thermoeconomic Environment is affected. Therefore, residues and sub-products have to be generally converted into some kind of product by different production processes, supporting the paradigm of the Circular Economy and highlighting the importance of recycling not only for system efficiency, but for system surviving. The results obtained may be regarded as the physical justifications of the evolutionary tendency toward the more and more complex and highly circular pathways that can be observed in both natural and artificial production systems.